Coach, parent, and administrator perspectives on required coaching education in organized youth sport - Bolter, N. D.; Jones Petranek, L.; Dorsch, T. E. (International Journal of Sports Science & Coaching, 2018)
Previous studies have primarily relied on coaches` perspectives about whether and how to provide formal coaching education in youth sport. This study was designed to highlight multiple perspectives from key stakeholders (i.e., coaches, parents, and administrators) about the need for required formal coaching education programs in a youth sport community. We applied Bronfenbrenner`s process-person-context-time framework to understand views on required coaching education and children`s development through sport from an ecological vantage. The sample included 202 coaches, 309 parents, and 38 administrators who were involved in youth sport. In an online survey, participants were asked whether they agreed or disagreed that coaching education should be required, followed by an open-ended question asking them to elaborate on their answer. Quantitatively, the majority of participants agreed or strongly agreed that coaching education should be required. Inductive-deductive qualitative analyses resulted in 49 lower order themes representing 11 higher order themes that spanned the four categories of the process-person-context-time framework. Themes highlighted both convergence and divergence among the perspectives of coaches, parents, and administrators about why coaching education should or should not be required.